English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

Distribute, and use the property (ab)^x = a^x b^x:

12m^(-4)m^6 - 3m^(-4)m^5 + 5^2 m^2

Use a^x a^y = a^(x+y):

12m^2 - 3m + 25m^2

Combine like terms:

37m^2 - 3m

2006-10-26 14:07:12 · answer #1 · answered by James L 5 · 0 0

3m^-4 (4m^6-m^5)+(5m)^2=
(3/m^4)(4m^6-m^5)+25m^2=
12(m^6/m^4) - 3(m^5/m^4) + 25m^2=
12m^2 - 3m + 25m^2=
37m^2-3m=
m(37m-3)

i may have made a mistake though

2006-10-26 21:09:46 · answer #2 · answered by Europa C 1 · 0 0

All you do is mulitply and add or subtract the powers depending on there signs.

Answer:

12m^2 -3x +25m^2
37m^2 -3m

2006-10-26 21:10:28 · answer #3 · answered by Infidel-E 2 · 0 0

was it correctly written????

2006-10-26 21:16:46 · answer #4 · answered by lazareh 2 · 0 0

fedest.com, questions and answers